2021
DOI: 10.22541/au.164004638.87453812/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asymptomatic Covid-19: a major source of infection at the onset of an Omicron storm 

Abstract: This is the first time since the pandemic began with isolated cases in the early fall of 2019 in the city of Wuhan (CCP-China) that health authorities have completely lost control of the pandemic’s development without having any tool to counteract this evolving event. Sars-CoV-2 Omicron is unstoppable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…We estimate that 59.8% of the positive tests were asymptomatic, where asymptomatic rates were similar among elementary school students (60.8%) and students in junior high and high schools (58.1%). Previous studies have reported asymptomatic rates associated with the Omicron variant to be between 32% and 44% [55], where asymptomatic rates tend to be higher in younger age groups [29, 47, 55]. Our high asymptomatic rates could be due to reporting errors.…”
Section: Discussionmentioning
confidence: 68%
“…We estimate that 59.8% of the positive tests were asymptomatic, where asymptomatic rates were similar among elementary school students (60.8%) and students in junior high and high schools (58.1%). Previous studies have reported asymptomatic rates associated with the Omicron variant to be between 32% and 44% [55], where asymptomatic rates tend to be higher in younger age groups [29, 47, 55]. Our high asymptomatic rates could be due to reporting errors.…”
Section: Discussionmentioning
confidence: 68%